2012
DOI: 10.1088/1757-899x/38/1/012012
|View full text |Cite
|
Sign up to set email alerts
|

Optical field-induced surface relief formation on chalcogenide and azo-benzene polymer films

Abstract: Abstract. The dependence of the surface relief formation in amorphous As 2 S 3 and Disperse Red 1dye grafted polyurethane polymer films on the polarization state of recording light was studied. It is shown that the direction of mass transport on the film surface is determined by the direction of light electric vector and photoinduced anisotropy in the film. We propose a photoinduced dielectropfhoretic model to explain the photoinduced mass transport in amorphous films. Model is based on the photoinduced soften… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 21 publications
0
1
0
Order By: Relevance
“…The largest SR modulation can be obtained with +45 o : -45 o and RCP: LCP recording beam configurations. Obtained results suggested that the whole illuminated volume of the film takes part in SRG formation process [10][11][12][13]. More profound studies showed the SRG formation dependencies on film thickness and grating period.…”
Section: Introductionmentioning
confidence: 91%
“…The largest SR modulation can be obtained with +45 o : -45 o and RCP: LCP recording beam configurations. Obtained results suggested that the whole illuminated volume of the film takes part in SRG formation process [10][11][12][13]. More profound studies showed the SRG formation dependencies on film thickness and grating period.…”
Section: Introductionmentioning
confidence: 91%